As idéias políticas e a apologética de Ramon Llull (1232-1316) sobre a cruzada na Terra Santa - Ventorim, Eliane (2008)
Between the XII and XIV centuries, Occidental Christian Europe lived a period of large religious fervor. During these years we had the birth of many religious orders, as well as military orders, and all of this was related to a need of reform of the Christianity as well as the recovery of sacred territories to the Christianity that had fallen in hands of unfaithful. It was on this context of changes and reforms that Ramon Llull lived. Born in the Majorca Island, a border region, he had daily contact with the unfaithful. When Ramon, by divine will, converted himself, he decided to give his life to Christ. By his passion to Christ, Lull assumed an important mission: to prove in a rational form that the Christianity was the only true religion. To go through this project, it was necessary, first of all, to achieve the unification of the Christianity, divided in many factions, for after that, to convert the unfaithful to the Latin creed. This project had an intern division: the spiritual crusade and de corporal crusade. It is through the work of the “unfaithful solicitor”, written between 1289 and 1309, mainly the Book of the End (1305) that I intend to enter this life full of works, writings, moans and hopes.